Two decades of structural transformation and dynamics of income equality in indonesia - Teguh Dartanto; Edith Zheng Wen Yuan; Yusuf Sofiyandi (Asian Development Bank Institute (ADBI), 2017)
Successful reductions in poverty, resulting from substantial increases in income and structural transformation, have been associated with growing levels of income inequality. This paper explores the link between structural transformation and inequality in Indonesia by applying Theil's L decomposition (both static and dynamic) to the National Socio-Economic Surveys of 1996, 2005, and 2014 and panel data analysis of provincial macroeconomic datasets. This study confirms that, as has been seen in other developing countries, Indonesia has experienced an agriculture-service transition, before the industry sector has matured. Moreover, the Inverted U Kuznet curve exists in Indonesia. Inequality will increase in tandem with an increase in per capita income until it reaches an income level beyond which the inequality starts to decline. From both static and dynamic decomposition of Theils's L, this study found that (i) the root cause of increasing inequality in Indonesia is the pure inequality effect (unexplained effect); (ii) population shifts from the agriculture sector to either the industry or service sectors, from rural to urban areas and from informal to formal employment are the second contributor to explain increases in inequality; (iii) an increase in educational attainment has also contributed to increasing inequality during the last 2 decades; and (iv) even though the contribution is cancelled out, increasing inequality has been curbed by the growing income from those working in the agriculture sector, in the informal sector, by those living in rural areas, and by those without formal education. Finally, our estimation results suggest that the structural transformation of economic development was responsible for the growing inequality in Indonesia. Nevertheless, the increasing share of service sector to the national gross domestic product has degraded the growth rate of inequality during the observation period.
Keywords: D63; L16; O15; O53; 330; inequality; Gini Index; Theils; decomposition; Indonesia